Integrated pest management options for the fall armyworm Spodoptera frugiperda in West Africa: Challenges and opportunities. A review - Besmer Régis Ahissou (Presses Agronomiques de Gembloux, 2021)
Introduction. The fall armyworm Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) is a voracious and generalist insect pest native to America. It was first detected in West Africa in 2016 and rapidly spread across the continent. The indiscriminate use of chemical insecticides poses risks to human health and threatens the few natural enemies present in these environments. Despite the existence of alternative control measures in America (e.g. genetically modified maize), efforts are needed to develop environmentally friendly approaches that are affordable for smallholder farmers and compatible with the African context.